Formulation and Evaluation of Gabapentin Mucoadhesive Gastro Retentive Tablets. - M.Vikramaditya Reddy; Ch.S.Vijayavani; V.Uma Maheshwara Rao (IJPAR JOURNAL, 2013)
The present research work was an attempt to Formulate and Evaluate Gabapentin Gastroretentive mucoadhesive tablets to prolong gastric residence time and increase drug absorption further increasing the bioavailability. The tablets were prepared by direct compression method using mucoadhesive polymers like Carbopol 934P, Sodium Carboxy Methyl Cellulose (SCMC), Sodium alginate along with other standard excipients like Microcrystalline cellulose, Magnesium stearate and Aerosil . FTIR studies confirmed the absence of any drug/polymers/excipients interactions. The prepared tablets were evaluated by different parameters such as Thickness, Weight variation, Hardness, Content Uniformity, Swelling Index and Mucoadhesive strength. Indigenously fabricated assembly was used to measure the Mucoadhesive strength of the Mucoadhesive tablets, and goat gastric mucosa was used as a model tissue. Mucoadhesive strength increased with increasing Polymer concentrations. The tablets were also evaluated for in vitro drug release in 0.1N HCl for 12 h in USP Type II dissolution apparatus. Among all the formulations (F-I to F-XII) prepared, batch F-IV (0.5% C-934P) gave relatively slow release of Gabapentin over 12 h when compared to other formulations The in-vitro data is fitted in to different kinetic models and the best-fit was achieved with the Peppas model. The optimized formulation F-IV followed Zero order release kinetics followed by non-fickian transport. Mucoadhesive tests assured the prolonged Gastro retention of tablets. It also showed no significant change in physical appearance, Drug content, Mucoadhesive strength or in-vitro dissolution pattern after storage at 450 C at 75 % RH for a period of 3 months.